2004
DOI: 10.1038/sj.bjc.6601536
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the epidermal growth factor receptor family in prostate carcinoma before and during androgen-independence

Abstract: Novel palliative strategies for patients with androgen-independent prostate cancer (AIPC) include targeting the epidermal growth factor receptor (EGFR) family. The aim of the present study was to investigate intrapatient changes of EGFRs during the development of AIPC. In total, 106 symptomatic AIPC patients were identified in whom prostatic biopsies (adenocarcinoma) were available both before the start of androgen deprivation (PRTR biopsy) and after the development of AIPC (AIPC biopsy). All four known subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
110
4

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 22 publications
(27 reference statements)
9
110
4
Order By: Relevance
“…Furthermore, in prostate cancer cell lines, we found that androgen-sensitive LNCaP cells and castration-resistant C4-2 cells also overexpressed this protein (Figure 3). Our findings are consistent with the majority of patient-related reports in literature, [5][6][7][8]10,11 as well as some in vitro and animal model studies. 13,48,49 Furthermore, it has been recently reported that in men with long-term follow-up after HER-2 targeting of prostate cancer K-x Zhang et al radical prostatectomy, HER-2 expression when combined with percentage DNA index can be used clinically for prediction of progression, metastasis and prostate cancerspecific death.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, in prostate cancer cell lines, we found that androgen-sensitive LNCaP cells and castration-resistant C4-2 cells also overexpressed this protein (Figure 3). Our findings are consistent with the majority of patient-related reports in literature, [5][6][7][8]10,11 as well as some in vitro and animal model studies. 13,48,49 Furthermore, it has been recently reported that in men with long-term follow-up after HER-2 targeting of prostate cancer K-x Zhang et al radical prostatectomy, HER-2 expression when combined with percentage DNA index can be used clinically for prediction of progression, metastasis and prostate cancerspecific death.…”
Section: Discussionsupporting
confidence: 93%
“…In prostate cancers, overexpression of HER-2 has been reported to be associated with progression to androgen independence, [5][6][7][8]10,11 although some contradictory results have also been reported. 39,40 To normalize variables such as fixation and staining procedures, which could account for the reported differences, we used a TMA approach where 105 unique prostate tissue cores from 35 patients were immunostained for HER-2 simultaneously.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bs affibody molecule should also have the potential to target two tumourassociated target proteins on the same cell. For certain tumour types, variable expression levels, but rather frequent expression, of both HER2 and EGFR have been reported [14][15][16][17][18][19], and bs targeting could thus be a valuable strategy to increase the efficiency in cancer imaging or therapy.…”
Section: Discussionmentioning
confidence: 99%